If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 64 = 9u + -1u Combine like terms: 9u + -1u = 8u 64 = 8u Solving 64 = 8u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-8u' to each side of the equation. 64 + -8u = 8u + -8u Combine like terms: 8u + -8u = 0 64 + -8u = 0 Add '-64' to each side of the equation. 64 + -64 + -8u = 0 + -64 Combine like terms: 64 + -64 = 0 0 + -8u = 0 + -64 -8u = 0 + -64 Combine like terms: 0 + -64 = -64 -8u = -64 Divide each side by '-8'. u = 8 Simplifying u = 8
| 103+5x=63 | | 2(x)=54 | | x/-6=120 | | 2y+16=48 | | 2x-2-3=21-34x | | 31+4x=86 | | xln(x)-1=0 | | -54-8x=2x | | (1.09^x)/50 | | 4/5/5/4= | | v=1/3*b*h | | 7n-3n=3n+15 | | 3-12x+18=33 | | 9x-10y=24 | | -4-8=4(-3n+2) | | 9x-11=3x+8 | | 4x(3-y)=0 | | x+5(x-2)=8 | | 24+3x=3x(7-1) | | 9n+1=10 | | 10x=2+5 | | X-0.2x=520 | | 6x+29=-25 | | f(x)=x-(3/lnx) | | f(x)=x-3/lnx | | 18x-5x+4=28 | | 8x-(6x+5)=4x-21 | | 4x+2=(x-5) | | 4y+2=3(y-5) | | 3(3+3x)=8(x-2) | | 3(3+3)=8(x-2) | | 6x/2-3 |